Cytomegalovirus disease in immunocompetent adults. Issue 10 (17th November 2014) - Lancini, Daniel; Faddy, Helen M; Flower, Robert; Hogan, Chris
Summary: Cytomegalovirus (CMV) is a highly prevalent and globally distributed virus. CMV infection in healthy adults is usually asymptomatic or causes a mild mononucleosis‐like syndrome. CMV disease causes significant morbidity and mortality in neonates and severely immunocompromised adults. CMV disease can present with a wide range of manifestations, with colitis being the most common. The incidence of severe CMV disease in immunocompetent adults appears to be greater than previously thought, which may be partly due to immune dysfunction related to comorbidities such as kidney disease or diabetes mellitus. CMV disease can mimic an array of alternative diagnoses and pose a significant diagnostic challenge, especially in immunocompetent adults, leading to delayed diagnosis, adverse health outcomes and unnecessary financial expense. Non‐invasive testing for CMV is widely available and can facilitate early diagnosis if used appropriately. Although limited, current evidence suggests that targeted antiviral therapy with ganciclovir or valganciclovir is appropriate for severe CMV disease in immunocompetent adults.